Hydrodynamic performance of a novel oscillating-water-column breakwater with a horizontal bottom-plate: Experimental and numerical study. (1st September 2019) - Deng, Zhengzhi; Ren, Xiang; Wang, Lixian; Wang, Peng
Abstract: In this study, the hydrodynamic characteristics of a novel oscillating water column (OWC) breakwater with a horizontal bottom-plate is numerically and experimentally investigated. A viscous fully nonlinear numerical wave tank (NWT) solved by the open source package OpenFOAM is established under laminar flow conditions. After comparing the numerical results with the experimental ones, the well-validated numerical model is further employed to investigate the effects of the length of horizontal bottom-plate ( D ), the immersion depth of back-plate ( d 2 ), the water depth ( h ) and the wave height ( H ) on the reflection ( C r ) and transmission ( C t ) coefficients, dissipation coefficient ( C d ) and column-confined energy coefficient ( C e ) of the breakwater. The results show that lengthening the bottom-plate can effectively increase the energy dissipation and then lead to lower reflection and transmission coefficients, and a smaller draught of the back-plate can also increase energy dissipation. The water depth has insignificant influence on the hydrodynamic coefficient of long waves, but influences the breakwater performance in short waves. The variation of wave height mainly contributes to the change of reflection coefficient. Highlights: A novel OWC breakwater with a flat bottom-plate is investigated experimentally. Numerical simulations with a CFD solver are used to extend the experimental database. An optimal performance of the proposed OWC breakwater is presented and discussed.